Effective Components of Panax quinquefolius and Corydalis tuber Protect Myocardium through Attenuating Oxidative Stress and Endoplasmic Reticulum Stress. (24th June 2013) - Xue, Mei; Liu, Meilin; Zhu, Xinyuan; Yang, Lin; Miao, Yu; Shi, Dazhuo; Yin, Huijun
Abstract : Both oxidative stress and endoplasmic reticulum stress (ERS) have been implicated in carcinogenesis and neurological diseases, while there are few reports about the mechanisms of them in the progression of acute myocardial infarction (AMI). This study examined oxidative stress and ERS in a rat model of AMI and evaluated their role in therapy by metoprolol and effective components of Panax quinquefolius and Corydalis tuber (EPC). In the present study a rat model of AMI was established by ligation of the left anterior descending coronary artery. After oral administration of metoprolol or low-to-high doses of EPC for 2 weeks, serum malondialdehyde (MDA), superoxide dismutase (SOD), and 8-iso-prostaglandin F2 α (8-iso-PGF2 α ) were detected using enzyme-linked immunosorbent assay (ELISA). Quantitative real-time PCR and Western blotting were used to examine mRNA and protein expressions of the hallmarks of ERS-glucose-regulated protein-78 (GRP78) and CCAAT/enhancer-binding protein homologous protein (CHOP). We confirmed that both metoprolol and moderate-to-high dose of EPC decreased 8-iso-PGF2 α serum level and downregulated the mRNA and protein expressions of GRP78 and CHOP in myocardium, while EPC also increased SOD serum level. These results indicated that metoprolol and EPC protect the myocardium by attenuating oxidative stress and ERS induced by myocardial infarction, highlighting the ERS pathways as potential therapeutic targets for AMI.